Galangin, a dietary flavonoid, ameliorates hyperglycaemia and lipid abnormalities in rats with streptozotocin-induced hyperglycaemia - Aloud, Amal A.; Chinnadurai, Veeramani; Govindasamy, Chandramohan; Alsaif, Mohammed A.; Al-Numair, Khalid S. (Pharmaceutical biology, 2018)
Context: Galangin, a natural flavonoid, is found in honey and Alpinia officinarum Hance (Zingiberaceae). Galangin has antiviral, antimicrobial, antidiabetic and anticancer properties, without side effects. The effects of galangin on hyperglycaemia and lipid abnormalities are not known. Objective: To elucidate the effectiveness of galangin on hyperglycaemia-associated complications and lipid changes in rats with streptozotocin (STZ)-induced hyperglycaemia. Materials and methods: Diabetes was induced in adult Wistar rats by administering 40 mg/kg of STZ. In our previous study, galangin had no toxicity at concentrations up to 320 mg/kg. Therefore three doses of galangin (4, 8 or 16 mg/kg BW) or glibenclamide (600 µg/kg BW) were administered daily to diabetic rats orally for 45 days. Results: Diabetic rats showed a significant (p < 0.05) increased levels of plasma glucose (281.10 mg/dL) and decreased levels of insulin (6.01 μU/mL). Additionally, diabetic rats showed a significant (p < 0.05) increased levels of plasma lipid profiles such as total cholesterol (149.05 mg/dL), triglycerides (143.28 mg/dL), free fatty acids (139.37 mg/dL), phospholipids (127.53 mg/dL), plasma low-density lipoprotein-cholesterol (98.72 mg/dL), plasma very low-density lipoprotein-cholesterol (28.65 mg/dL), and significant (p < 0.05) decreased in plasma high-density lipoprotein-cholesterol (21.68 mg/dL). When galangin was administered to the hyperglycaemic rats, plasma glucose and insulin levels and lipid profiles reverted to levels similar to those in healthy control rats. Discussion and conclusions: Administration of galangin reduced hyperlipidaemia related to the risk of diabetic complications and could be beneficial for diabetic hyperlipidaemic patients. Further work detailing its mechanism-of-action for improving hyperglycaemic-associated lipid abnormalities is needed.